The Influences of Ambidexterity, New Public Management and Innovation on the Public Service Quality of Government Organizations - Alkaabi, Seema; Hazzam, Joe; Wilkins, Stephen; Dan, Sorin (Taylor & Francis, 2024)
This study assesses the influences of organizational ambidexterity and new public management (NPM) innovations on public service quality in the under-researched and changing context of the Arabian Peninsula Gulf States. The data used were obtained from government organizations in the Sultanate of Oman and were analyzed using structural equation modeling. The findings indicate that exploitation is associated with public service quality and this relationship is partially mediated by public service innovation. The results show an indirect relationship between NPM practices and service quality mediated by service innovation. Moreover, the relationship between exploration and service quality is fully mediated by service innovation. This study extends the existing research on ambidexterity in government organizations and contributes to the international public administration reform and innovation literature by examining the applicability of Western practices in changing societal and politico-administrative cultures.
Keywords: public service quality; public service innovation; ambidexterity; exploration; exploitation; new public management; fi=Julkisjohtaminen|en=Public Management|